P-239 Tomorrow's carers – helping to unlock their potential!. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Wilcocks, Tricia; Marshall, Sue
Abstract : Background: The hospice identified previous work placements offered internally provided an inconsistency of experience for learners, with multiple requests placing a burden on care staff, resulting in a review of the model of student support. This closely related to influential factors for future work force planning as follows: increasing demand on health and social care services; growing role of hospices as educators; a need to influence student career choices as early as possible; reluctance to expose young people to direct care. To extend opportunities, funding was obtained from Health Education England to trial different models of support. Aims: Increase number of students experiencing hospice care Provide alternative structured training models Provide consistent positive experience of care delivery Support workforce to stimulate student's experiences. Approach: Comparison of two supported training models: One week accredited course Six month placement. A student's conclusion – "I was relieved to find out we were being taught valuable skills on an actual course, not just making teas." Conclusion: From successful pilot, we expect the following outcomes to shape future training: Increase in students accessing and considering a career in care Identify best approach to support students Portable qualifications achieved Focused opportunity for staff to support students.